Case report: A novel TLK2 variant with a neuropsychiatric phenotype from a Chinese family - Huang, Hongmei; Qian, Yue; Yang, Chenlu; Li, Shijie (Frontiers in Genetics, 2024)
Background Tousled-like kinase 2 (TLK2) gene variant-related neurodevelopmental disorder was recently described. The haploinsufficiency of TLK2 was considered the most likely underlying disease mechanism, leading to a consistent neurodevelopmental phenotype. So far, only four studies, conducted on 49 patients from North America and Europe, have been reported. Case presentation In this study, we reported a Chinese family with a TLK2-related neuropsychiatric phenotype. The proband, a boy aged 2 years and 6 months, presented with temper tantrums, mood lability, aggressiveness, congenital astigmatism, and distinctive facial dysmorphism. Whole-exome sequencing identified a novel heterozygous variation in TLK2 gene (c.49dupG, p. E17Gfs*10) in them. His father carried the same TLK2 gene variant and exhibited anxiety and irritability. The parental grandparents and other family members had no such variation. Moreover, the proband was found to have global developmental delay, autism-like symptoms, and mild elevated homo-vanillic acid (HVA) and 2,3-dihydroxy-2-methylbutyric acid levels tested in urine. Conclusion Herein, we identified a novel TLK2 variant from a Chinese family and reported a new neuropsychiatric phenotype. This study also expanded the genotype profile of the newly defined TLK2-related neurodevelopmental disorder.